Impact of Primary Immunodeficiency Diseases on the Life Experiences of Patients in Malaysia From the Caregivers’ Perspective: A Qualitative Study - Ahmed Meelad, Ruwaydah; Abd Hamid, Intan Juliana; Hashim, Ilie Fadzilah; Zainudeen, Zarina Thasneem; Abu Bakar, Firdaus Farhani; Taib, Fahisham; Mohamad, Norsarwany; Mangantig, Ernest; Ismail, Intan Hakimah; Abdul Latiff, Amir Hamzah; Mohd Noh, Lokman (Frontiers in Pediatrics, 2022)
Introduction: Primary immunodeficiency diseases (PIDs) are chronic diseases that affect various aspects of a patient’s life. However, the impact of living with PIDs is poorly described. Objective: This study aimed to explore living experiences challenges among Malaysian caregivers of patients with PID who underwent follow-up in Universiti Sains Malaysia (USM) or those registered members of the Malaysian Primary Immunodeficiency Diseases Society (MyPOPI). Methodology: The study was conducted from 1 March until 30 May 2021. The parents of children with PIDs were invited to participate for a semi-structured in-depth interview at the PID clinics in USM. The estimated time of each interview was 30 minutes. The semi-structured interview was performed via telephone call becasue of COVID-19 pandemic restrictions. The audio recording of each interview was transcribed and translated from Malay to English. Subsequently, thematic analysis utilising ATLAS.ti software was performed. Result: The thematic analysis revealed five main themes, which are living with fear and anxiety with four sub-themes (sickness, psychological issues, fear of infections and hereditary issues), PID healthcare support struggles with four sub-themes (PID health system, treatment, diagnosis and financial issues), knowledge with two sub-themes (educational issues and disease understanding), social constraint with two sub-themes (relationships, and social isolations) and coping with three sub-themes (acceptance, child health improvement and emotional hygiene ). Conclusion: Living with fear and anxiety is a major theme impacting the living experiences of Malaysian patients with PIDs. Improvements in healthcare delivery and disease education are needed to ensure optimal quality of life.